2020
DOI: 10.3390/brainsci10080534
|View full text |Cite
|
Sign up to set email alerts
|

Localization of ZIP14 and ZIP8 in HIBCPP Cells

Abstract: The blood–cerebrospinal fluid barrier (BCB) is important in maintaining brain manganese (Mn) homeostasis. This barrier consists of a single layer of epithelial cells, connected by tight junctions, that restrict the passage of nutrients to only allow molecules to be carried through the membrane by a transporter. These epithelial cells are polarized with asymmetrical blood-facing and cerebrospinal fluid-facing sides. Here, we have established a polarized model of a human choroid plexus papilloma cell line, HIBCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
(93 reference statements)
2
5
0
Order By: Relevance
“…We also demonstrated that whereas ZIP8 was equally abundant in the apical (blood) and basolateral (abluminal) membranes of hBMVECs grown in transwells, 90% of plasma membrane–associated ZIP14 was found on the ‘brain’ side of this model BBB. A comparable asymmetric localization has been reported for these two transporters in the HIBCPP choroid plexus cell line ( 41 ). That these two transporters might contribute differentially to cellular manganese homeostasis was indicated also by differences in the regulation of their plasma membrane localization.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We also demonstrated that whereas ZIP8 was equally abundant in the apical (blood) and basolateral (abluminal) membranes of hBMVECs grown in transwells, 90% of plasma membrane–associated ZIP14 was found on the ‘brain’ side of this model BBB. A comparable asymmetric localization has been reported for these two transporters in the HIBCPP choroid plexus cell line ( 41 ). That these two transporters might contribute differentially to cellular manganese homeostasis was indicated also by differences in the regulation of their plasma membrane localization.…”
Section: Discussionsupporting
confidence: 83%
“…A similar pattern of ZIP8 re-localization from primarily intracellular to cell surface presentation was observed in HEK293 cells treated with iron (38). Note, however, that in hBMVECs, only a small fraction of total ZIP8 is in the plasma membrane compared to total cellular protein, a finding reported also in the A549 lung epithelial and HIBCPP choroid plexus papilloma cell lines (41,42), and human proximal tubular epithelial cells (43). In addition, the pattern of ZIP8 and ZIP14 cell localization observed in these latter cells is equivalent to the results shown herein.…”
Section: Calcium Induces a Perinuclear To Trans-golgi Trafficking Of ...supporting
confidence: 75%
See 1 more Smart Citation
“…ZIP8 in the brain microvascular capillary endothelial cells also plays a critical role in Mn uptake into the brain [ 53 ]. ZIP8 expression is enriched at the apical side of human choroid plexus papilloma cells, which are related to the blood-cerebrospinal fluid (CSF) barrier, contributing to Mn accumulation in these cells [ 54 ]. These findings suggest that ZIP8 transporter is important in Mn transport into the brain.…”
Section: Mn Transport To the Brainmentioning
confidence: 99%
“…A zebrafish model lacking ZIP14 accumulated higher Mn levels in the brain compared to those in wild-type (WT), leading to altered locomotor activity [ 58 ]. ZIP14 is enriched on the basolateral side of choroid plexus cells, contributing to Mn transport through these cells and the subsequent excretion [ 54 ]. ZIP14 mutation caused Mn accumulation in early-onset parkinsonism dystonia patients, suggesting the important role of ZIP14 in the regulation of Mn levels in the brain to prevent Mn neurotoxicity in humans [ 58 ].…”
Section: Mn Transport To the Brainmentioning
confidence: 99%